Penerapan Internet of Things (IoT) sebagai Sistem Monitoring dan Controller pada Kematangan Kerupuk Bandung - Ihsan Ihsan; Angga Wahyu Aditya (Emitor: Jurnal Teknik Elektro, 2023)
In the process of making Bandung Crackers whose interest and existence are still visible in all regions in Indonesia, a method is needed that can help determine the right level of maturity to help make the work of employees in the industry easier. Therefore, the authors compiled this scientific research using a quantitative method that aims to find and design a controller tool systematically based on the Internet of Things (IoT) system, so that revolutionary technology for the industry can develop. Researchers used a monitoring tool in the form of a Type-K Thermocouple Sensor to read the temperature in the boiler, along with the OLED and the Blynk application, as well as the Buzzer Output. Broadly speaking, the Controller tool uses the Blynk application by moving a Servo Motor that has been integrated with the stove knob to adjust the small and large fire remotely. The application of Monitoring and Controller tools in this study is expected to facilitate and provide a sense of security for workers in the Bandung Cracker industry. Through the design of the tools and applications used, researchers can see the temperature from a distance of 1-5 meters. This makes it easy to find out the maturity time during the Bandung Crackers drying process at 1000C as an indicator of proper maturity.